Developing the Core Pillars of Training Global Cardiovascular Health Researchers: Companionship, Light, and Fuel - Yan, Lijing L. (2019)
The 3 pillars that are effective in improving trainee performance and retention among busy early career investigators are companionship, light, and fuel.The research training process is a long-term journey where having companionship from peers and senior colleagues is essential.Strong mentorship provides light along the way whose successes can serve as lighthouses and beacons while illuminating the paths of early career investigators.Seed grants enable trainees to actually do research, applying what they have learned into practice to make a difference in global cardiovascular health.